Photo physical studies of PVP arrested ZnS quantum dots - Shahi A.K.; Pandey B.K.; Singh B.P.; Gupta B.K.; Singh S.; Gopal R. (My University, 2025)
Monodispersed polyvinylpyrrolidone (PVP) arrested ZnS quantum dots (QDs) having diameter in range ~2-5 nm are synthesized by a colloidal precipitation method using PVP as the stabilizing agent. X-ray diffraction (XRD), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), selective area electron diffraction (SAED) and Fourier transform infrared (FT-IR) spectroscopy are probed to investigate the structural information. The optical properties are studied using diffuse UV-visible reflectance and photoluminescence (PL) spectroscopy techniques. TEM images as well as XRD reflection peak broadening indicate the nanometer size particles formation with cubic (sphalerite) phase within the polymer matrix. Optical absorbance studies reveal an excitonic peak at around ~310 nm dictates the effect of quantum confinement effect in the ZnS QDs. PL emission spectra for ZnS QDs in PVP exhibit four emission peaks at ~382 nm, ~414 nm, ~480 nm and ~527 nm are observed. These excitonic emissions from ZnS QDs are caused by the interstitial sulfur/Zn vacancies and surface states. [Figure not available: see fulltext.] © 2017, The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.